Rethinking bail court reform or business as usual? - Travers, Max; Colvin, Emma; Bartkowska, Beata 1968-; Sarre, Rick 1955-; Day, Andrew; Bond, Christine (Springer International Publishing, 2020)
This book arises from a research project funded in Australia by the Criminology Research Council. The topic, bail reform, has attracted attention from criminologists and law reformers over many years. In the USA, a reform movement has argued that risk analysis and pre-trial services should replace the bail bond system (the state of California may introduce this system in 2020). In the United Kingdom, Europe and Australia, there have been concerns about tough bail laws that have contributed to a rise in imprisonment rates. The approach in this book is distinctive. The inter-disciplinary authors include criminologists, an academic lawyer and a forensic psychologist together with qualitative researchers with backgrounds in sociology and anthropology. The book advances a policy argument through presenting descriptive statistics, interviews with practitioners and detailed accounts of bail applications and their outcomes. There is discussion of methodological issues throughout the book, including the challenges of obtaining data from the courts
1. Introduction -- 2. Bail Reform In Context -- 3. Researching Bail Practices -- 4. Professional Perspectives -- 5. Bail Decision-Making -- 6. Defendants With Vulnerabilities -- 7. Risk Profiles.-8. Pretrial Services -- 9. Prospects For Court Reform -- 10. Conclusion: Rethinking Bail
Keywords: Corrections; Punishment; Criminal justice, Administration of; Forensic psychology; Crime-Sociological aspects; Criminal law; Public safety